Kesejahteraan Lansia Muslim Dan Nonmuslim Di Nagori Bosar Kecamatan Panombeian Panei Kabupaten Simalungun Sumatera Utara - Nahdah Ranuri Purba Nahdah (JAROW: Journal of Ar-Raniry on Social Work, 2023)
The elderly are citizens who need more attention. Currently the number of elderly people in Indonesia reaches 10.48% of the total population based on the BPS National Census Survey in March 2022. This research uses qualitative research with descriptive research type. After conducting research, there were research results which showed that the welfare of Muslim and non-Muslim elderly in Nagori Bosar, Panombeian Panei District, Simalungun Regency was dominated by non-Muslim elderly, especially in terms of indicators of health, education, and housing and home facilities. Researchers looked at health aspects such as history of disease, availability of health services, distance traveled to health service locations, education, namely the level of education completed, employment, such as type of work and amount of income, levels and patterns of consumption, namely expenditure incurred for both food and non-food needs. Housing and house facilities which include house ownership, type of house, house yard, water source, toilets and electronic devices